2014
DOI: 10.22401/jnus.17.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Study of Some [N-substituted] p-aminoazobenzene as Corrosion Inhibitors for Mild-Steel in 1M H2SO4

Abstract: Azo dye derivatives were prepared as corrosion inhibitors for mild steel in 1M H2SO4 solution by weighting loss measurements as evaluation tools. It has been observed that inhibition efficiency orders are A1> A3> A2with the highest inhibiting efficiency of 82% for 10 −3 M. Increasing in inhibitor concentration accompanies with corrosion rate decreases, inhibition efficiencies increase and surface coverage degree increases. Semi-empirical molecular orbital calculations of prepared compounds A1, A2, and A3 as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, these parameters also examine the spontaneity of a reaction, its energy profile, that is, either endothermic or exothermic, and describe temperature effects on different thermodynamic properties. It was observed that entropy, heat capacity, and enthalpy increase as temperature rises (Akinbulumo et al, 2020, Al-Doori andShihab, 2014). Whereas, free energy decreases with increasing temperatures.…”
Section: Thermodynamic Parametersmentioning
confidence: 99%
“…Furthermore, these parameters also examine the spontaneity of a reaction, its energy profile, that is, either endothermic or exothermic, and describe temperature effects on different thermodynamic properties. It was observed that entropy, heat capacity, and enthalpy increase as temperature rises (Akinbulumo et al, 2020, Al-Doori andShihab, 2014). Whereas, free energy decreases with increasing temperatures.…”
Section: Thermodynamic Parametersmentioning
confidence: 99%
“…Thus, there is a greater need to protect the materials used. Many researchers have attempted to develop methods for decreasing corrosion on metals [1][2]. The metallic materials react with their surrounding media based on the electrochemical corrosion process.…”
Section: ■ Introductionmentioning
confidence: 99%